The Effects of Bank-Level and Macroeconomic Variables on Commercial Bank Lending Based on Type of Use - Arintoko Arintoko (Journal of Economics, Business, and Accountancy Ventura, 2021)
ABSTRACTThe purpose of this study was to analyze the effect of interest rates, bank-level and macroeconomic variables on bank lending based on the type of use. The analysis method uses an autoregressive distributed lag (ARDL) model with quarterly data for the period of 2011Q1 - 2020Q1. The results show that investment lending behavior can be explained well by all bank-level and macroeconomic variables for the long run. The bank-level variable also reflects the performance and soundness of the bank, namely the capital adequacy ratio and loan to deposit ratio. Meanwhile, macroeconomic variables include inflation and real GDP. Consumer lending behavior is better explained by macroeconomic variables than bank-level variables. Meanwhile, GDP is the only variable that has a significant effect on working capital loans, which means that the behavior of working capital loans is more influenced by the business cycle as indicated by changes in real GDP. GDP is the only variable that consistently has a significant positive effect on bank loans for the three types of loans. Banks need to continue to emphasize the principle of prudence in providing credit by taking into account the term and credit risk, as well as internal and external factors.